2022
DOI: 10.1002/slct.202200128
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Synthesis of Triazole Analogues of Lavendustin A via Click Chemistry Approach and Preliminary Evaluation of Their Antiparasitic Activity Against Trypanosoma cruzi

Abstract: Lavendustin A is a natural product isolated from the actinobacteria Streptomyces griseolavendus that presents a potent inhibitory activity on the Epidermal Growth Factor Receptor Protein Tyrosine Kinase (EGFR PTK). In addition, some of its analogues have also shown potent inhibitory activity against the polymerization of tubulin to microtubules, a pivotal process for the cell mitosis. From strategic structural modifications, two useful unprecedented alkynes bearing lavendustin A pharmacophoric subunit were rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…As a result of their antiproliferative activity for the breast cancer stem cells, four triazole products exhibited much more potent activity than promising starting material Ironomycin. By following a similar approach, Carvalho et al [76] tried to get higher biological activity by modifying Lavendustin A, a natural product that presents strong tyrosine kinase inhibitory feature along with anticancer activity (Figure 7). Also, inspired by the antiproliferative and anti-infective activities of its synthetic derivatives, they searched for the antiprotozoal activity of ten triazole bioisosteric analogs of Lavendustin A.…”
Section: Design Synthesis Properties and Applications Of 123-triazolesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of their antiproliferative activity for the breast cancer stem cells, four triazole products exhibited much more potent activity than promising starting material Ironomycin. By following a similar approach, Carvalho et al [76] tried to get higher biological activity by modifying Lavendustin A, a natural product that presents strong tyrosine kinase inhibitory feature along with anticancer activity (Figure 7). Also, inspired by the antiproliferative and anti-infective activities of its synthetic derivatives, they searched for the antiprotozoal activity of ten triazole bioisosteric analogs of Lavendustin A.…”
Section: Design Synthesis Properties and Applications Of 123-triazolesmentioning
confidence: 99%
“…Within the context of nucleic acid-based therapeutics, the researchers reported that viral loads and virus induced cytotoxicity were reduced by five-fold by their siRNA in cell lines challenged with SARS-CoV-2. Analogs of Betulin CuAAC Anticancer activity [73] Analogs of Solithromycin CuAAC Antibacterial activity [74] Analogs of Salinomycin CuAAC Antiproliferative activity against cancer stem cells [75] Analogs of Lavendustin A CuAAC Antiprotozoal/antiparasitic activity [76] siRNA-peptide conjugate through alkyne containing RNA and azido-peptide CuAAC Anti-SARS-CoV-2 activity [77] Derived from enolizable carbonyl compounds, primary amines and 4-nitrophenyl azide…”
Section: Design Synthesis Properties and Applications Of 123-triazolesmentioning
confidence: 99%